F37 Effects of a partner's task on memory performance in Huntington's disease. (12th September 2022) - Fraisse, Nicolas; Dallery, Romain; Cléret de Langavant, Laurent; Youssov, Katia; Morgado, Graça; Schubert, Robin; Reilmann, Ralf; Busse, Monica; Craufurd, David; Rosser, Anne; Lunven, Marine; Bachoud-Lévi, Anne-Catherine
Abstract : Background: Individuals with Huntington's disease (HD) are impaired in paying attention to others' point of view, emotional states, and action. Such social capacities can be assessed by the shared memory task in which healthy participants improve their recall to items attributed to them (self-prioritization effect) or to a partner (joint-memory effect) rather than irrelevant ones (Eskenazi et al, 2013). Aim: We compared the magnitude of the effects of self-prioritization and joint memory between HD participants and controls. Methods: Sixty-nine HD and 56 control participants were enrolled from the Repair-HD cohort (NCT 03119246). During a semantic categorization task, they responded to words belonging to their assigned category. First, they were alone to respond and second, a partner was simultaneously performing the task. The three proposed semantic categories determined the social relevance of words (self, partner, irrelevant). This was followed by a free recall test of words. ANOVAs were performed to compare the two groups in terms of accuracy and response time to respond to words, the effects of self-prioritization and joint memory. Spearman's correlations assessed the relationship between these measures and traditional clinical scores. Results: HD participants responded faster to words when acting with the partner. As healthy controls, they exhibited both self-prioritization and Joint Memory effects. The extent of the latter correlated with cognitive scores. Conclusions: HD participants still pay attention to other. However, this capacity is impacted by their cognitive efficiency, which has implication for individual's care.